Iksodidni klopi, paraziti kuščaric (Lacertidae) v kraških in drugih predelih Jugoslavije - Tovornik, Danica (Scopolia, 1980)
The authors report on the infestation of lizards with ticks (Acarina: Ixodidae) in some parts of Yugoslavia. The lizards concerned some from Slovenia, Serbia incl. Vojvodina, Macedonia, Montenegro, but the majority, however, from the Adriatic West-Istrian, Quarner and Dalmatia islands. The tick survival in dry Karst regions, poor with vegetation during the hot summerperiod has been discussed. It has been established thet on the very small Adruatic islands and sea crags the blood source for unadult Haemaphysalis sulcata CANESTRINI et FAZAGO, are two lizard species, Lacerta melisellensis BRAUN and Lacerta sicula RAFINESQUE, which are often also the only vertebrate inghabitants of these habitats.
Keywords: klopi; Acarina; Ixodidae; ticks; karst; kras; Jugoslavija; Yugoslavia